2002
DOI: 10.4049/jimmunol.168.10.5024
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor FoxO Regulates Transcription of p27Kip1 and Bim in Response to IL-2

Abstract: The cytokine IL-2 plays a very important role in the proliferation and survival of activated T cells. These effects of IL-2 are dependent on signaling through the phosphatidylinositol 3-kinase (PI3K) pathway. We and others have shown that PI3K, through activation of protein kinase B/Akt, inhibits transcriptional activation by a number of forkhead transcription factors (FoxO1, FoxO3, and FoxO4). In this study we have investigated the role of these forkhead transcription factors in the IL-2-induced T cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
482
1
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(528 citation statements)
references
References 36 publications
37
482
1
8
Order By: Relevance
“…FOXOs suppress cell proliferation with transcription of the apoptosis-related and/or cellcycle inhibitor genes. p27 KIP1 is a target of transcription by FOXOs Stahl et al, 2002), and it induces cell-cycle arrest in any phase. In addition, the functions of p21 CIP1 and p27 KIP1 are inhibited by Aktdependent phosphorylation and translocation from nuclei to cytoplasm (Collado et al, 2000;Rodier et al, 2001;Zhou et al, 2001;Fujita et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOXOs suppress cell proliferation with transcription of the apoptosis-related and/or cellcycle inhibitor genes. p27 KIP1 is a target of transcription by FOXOs Stahl et al, 2002), and it induces cell-cycle arrest in any phase. In addition, the functions of p21 CIP1 and p27 KIP1 are inhibited by Aktdependent phosphorylation and translocation from nuclei to cytoplasm (Collado et al, 2000;Rodier et al, 2001;Zhou et al, 2001;Fujita et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Akt-dependent phosphorylation of FOXOs results in their cytoplasmic localization, possibly by association with 14-3-3 proteins, and inability to exhibit their gene transcriptional activity (Brunet et al, 1999;Woods and Rena, 2002). FOXOs are reported to be involved in apoptosis induction or cell-cycle arrest by transcription of the related genes Rokudai et al, 2002;Stahl et al, 2002;Suhara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As Bim is critical for cytokine deprivation-induced apoptosis in diverse hematopoietic cell subsets [5,16], it was concluded that growth factor withdrawal kills cells through transcriptional upregulation of Bim by Foxo3a [11][12][13][14].…”
Section: Identification Of Foxo-binding Sites In the Bim Promotersmentioning
confidence: 99%
“…Previous studies showed that cytokine deprivation activates Foxo3a and that the resulting apoptosis can be inhibited by expression of a dominant-negative Foxo3a [11][12][13]. It was therefore concluded that Foxo3a-mediated transcriptional induction of Bim is essential for cytokine deprivation-induced apoptosis.…”
Section: Bim Dfoxo/dfoxo Cells Die Normally By Cytokine Withdrawalmentioning
confidence: 99%
“…At the transcriptional level, the promoter of the Bim gene is activated by stress-inducible transcription factors including activator protein 1 and forkhead box protein O. 4,7,8 Post-transcriptional mechanisms that have been shown to control Bim expression levels include both mRNA stability 9 and protein stability. [10][11][12] Signaling downstream of receptor tyrosine kinases (RTKs) including epidermal growth factor receptor induce the proteasomal degradation of Bim.…”
mentioning
confidence: 99%